2022
DOI: 10.3847/1538-4357/ac713b
|View full text |Cite
|
Sign up to set email alerts
|

The Role of O+ and He+ in the Propagation of Kinetic Alfvén Waves in the Earth’s Inner Magnetosphere

Abstract: Interactions between plasma particles and electromagnetic waves play a crucial role in the dynamics and regulation of the state of space environments. From plasma physics theory, the characteristics of the waves and their interactions with the plasma strongly depend on the composition of the plasma, among other factors. In the case of the Earth’s magnetosphere, the plasma is usually composed of electrons, protons, O+ ions, and He+ ions, all with their particular properties and characteristics. Here, using plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Now, for the sake of investigation the QB relaxed state, we use the plasma parameters of the inner magnetosphere of the earth, where the ambient magnetic field and density of plasma species in 46$$ 4-6 $$ L$$ L- $$shells are as follows: B0=1.44×1034.87×103$$ {B}_0=1.44\times {10}^{-3}-4.87\times {10}^{-3} $$ gauss, ne=10$$ {n}_e=10 $$ cm −3 , np=45.8$$ {n}_p=4-5.8 $$ cm −3 , nh=0.21$$ {n}_h=0.2-1 $$ cm −3 , and ni=45$$ {n}_i=4-5 $$ cm −3 . [ 15,54 ] Firstly, in Figure 1 (i–iii), the condition normalΔ>0$$ \Delta >0 $$, normalΘ<0$$ \Theta <0 $$, and normalΓ<0$$ \Gamma <0 $$, is plotted as a function of Beltrami parameters of ion species (ap$$ {a}_p $$, ah$$ {a}_h $$, and ai$$ {a}_i $$) for the fixed value of ae=1.0…”
Section: Characteristics and Analytical Solution Of Qb Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…Now, for the sake of investigation the QB relaxed state, we use the plasma parameters of the inner magnetosphere of the earth, where the ambient magnetic field and density of plasma species in 46$$ 4-6 $$ L$$ L- $$shells are as follows: B0=1.44×1034.87×103$$ {B}_0=1.44\times {10}^{-3}-4.87\times {10}^{-3} $$ gauss, ne=10$$ {n}_e=10 $$ cm −3 , np=45.8$$ {n}_p=4-5.8 $$ cm −3 , nh=0.21$$ {n}_h=0.2-1 $$ cm −3 , and ni=45$$ {n}_i=4-5 $$ cm −3 . [ 15,54 ] Firstly, in Figure 1 (i–iii), the condition normalΔ>0$$ \Delta >0 $$, normalΘ<0$$ \Theta <0 $$, and normalΓ<0$$ \Gamma <0 $$, is plotted as a function of Beltrami parameters of ion species (ap$$ {a}_p $$, ah$$ {a}_h $$, and ai$$ {a}_i $$) for the fixed value of ae=1.0…”
Section: Characteristics and Analytical Solution Of Qb Statesmentioning
confidence: 99%
“…[1][2][3][4][5] In recent years, extensive research has been conducted on multi-ion plasmas in order to investigate various nonlinear structures. For instance, several researchers have studied ion cyclotron waves, [6][7][8][9][10] kinetic Alfvén waves, [11][12][13][14][15] electrostatic ion-cyclotron waves, [16] inertial Alfvén waves, [17] and oscillitons [18] in multi-ion plasmas containing three positive ion species that occur in various regions of the earth's magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…When disturbances occur in the Earth's magnetosphere, such as geomagnetic storms, heavy ions from the solar wind can penetrate the magnetosphere, affecting Earth's space environment (Kronberg et al 2014;Allen et al 2016). When the abundance of heavy ions in the magnetosphere changes, it will not only affect the propagation of Alfvén waves (Moya et al 2022), but also as high-energy particles are injected from the plasma layer into the magnetosphere, heavy ions play a key role in the generation of ring currents and radiation belts (Wang et al 2019). It has been suggested that when the abundance of oxygen ions is relatively high, it will lead to a significant thickening of the current sheet, and it has also been verified in other magnetospheres of Earthlike planets in the solar system (Domrin et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the abundance of ions in the plasma plays a crucial role in the interaction between the plasma particles and Alfvén waves. For instance, the propagation of Alfvén waves depends to a large extent on the relative abundance of He + and O + (Moya et al 2022). Besides, charge exchange collisions of solar wind heavy ions with geocoronal hydrogen atoms can generate extreme-ultraviolet and soft-X-ray emissions in the magnetosheath and cusp region, which can be effectively used to image the global structure of the bow shock and magnetopause (He et al 2015;Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the MHD Alfvén waves that show parallel propagation, the KAWs propagate nearly perpendicular to the ambient magnetic field (Barik et al 2019a). Further, KAWs exhibit right-handed polarization that distinguishes them from other plasma waves like electromagnetic ion cyclotron waves (Gary 1986;Narita et al 2020;Moya et al 2021Moya et al , 2022.…”
Section: Introductionmentioning
confidence: 99%